The Effect of Over Workload and Role Conflicts on Behavior of Tax Auditor Dysfunction with Working Stress as Mediation Factor and Moral Competence as Moderation Factor (Empirical study at Indonesian Directorate General of Taxes) - Kartika Cahya Kencana; Susanti Widhiastuti (Universitas Agung Podomoro, 2018)
This study examines the theory of transactional processes which applied work stress theory proposed by Gibson et al. (1995). The researcher collected data from tax auditors as participants using survey techniques by self-filling questionnaires. The qualitative data are converted into the parametric scale with the Method of Successive Interval and then analysed using Partial Least Square. The result of this study is work stress can mediate the effect of over workload and role conflict on tax auditor dysfunction behavior moral competence can not moderate the relationship of influence of work stress on dysfunction behavior. Surveys conducted are not accompanied by researcher in filling questionnaires in the theoretical sphere so as to generate potential bias in the results. This study produces a quality tax audit of the errors of professional humanism. For further research, can be analyzed by using the experimental method.